Family-Based Maternal Sensitivity Model as a Strategy to Optimize Family Perception on the Role of Parents and the Growth of Infants - Diyan Indriyani; Susi Wahyuning Asih (Universitas Airlangga, 2018)
Introduction: Family perceptions on the role of parents and the growth of infants must be seriously considered by healthcare workers since they can affect the role of family development in taking care of the babies. A family that has optimally understood the role of their development as a parent will be able to give the appropriate care for the babies.Methods: The study aimed to find out the effects of a family-based Maternal Sensitivity Models (MSM) strategy for family perception optimization on the role of parents and the growth of infants. It used a quasi-experimental design with the samples of 50 families. The samples were obtained using purposive sampling technique. The data were analyzed using dependent t-test.Results: It confirmed that the Family-Based Maternal Sensitivity Models (MSM) strategy significantly affects family perceptions on the role of parents with t-value 5.915 and p-value 0.000. MSM also significantly affects family perceptions on the growth infants with the t-value -11.257 and p-value 0.000.Conclusions: Maternal Sensitivity Models (MSM) can be well applied as one of the health models provided by healthcare workers to optimize parents’ perceptions and infants’ growth as well as to develop a competent family in giving care for their babies.